Analysis of Yeni Wahid's Interpretation as a political Comunicator at PKBIB - Selfiya, Nur Amilia Alimatul; Rukmini, Dyah; Fajrin, Saniah (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
This study dicusses the pattern of leadership and movement of a female political communicator, Zannuba Ariffah Rahman Wahid or know as Yenny Wahid, the daughter of the 4th President of the Republic of Indonesia. The pattern of leadership and movement of Yenny Wahid is interesting to study considering some of recent controversies with the Chairman of “the National Awakening Party” (PKB), Muhaimin Iskandar. Research objectives: 1. To describe the leadership style of a female political communicator, Yenny Wahid; 2. Explaining the actions of Yenny Wahid as the direct successor of Gus Dur in the realm of politics. Using a qualitative approach with a document or text study method. The result showed that Yenny Wahid made the figure of Gus Dur as a guide in leading and living life. thought that politic is a place for service, if the leader succed in making police for the progress of the people, then life will feel more meaningful. On the otherhand, as a woman and mother, Yenny never ignored her duties.